Formulasi Strategi Pengembangan Sumber Daya Manusia Perawatan Pesawat Terbang - Danny Ramdani (Universitas Winaya Mukti, 2019)
The lack of level human resources capabilities in narrow-body aircraft maintenance (Airbus & Boeing), which implies the achievement of all operator's maintenance revenue in Indonesia. The research focused on the business unit of Aircraft Services of Indonesian-aircraft Industries. The purpose of this study was to analysis and make a formulation strategy development of aircraft maintenance knowledge workers at the business unit of Aircraft Services of Indonesian-aircraft Industries. The research used a case study with a qualitative method and SWOT analysis used as a tool in the implementation process. The datas collect conducted through some literature, documents, and in-depth interviews. The subjects were managers, senior engineers, instructors, inspectors, technicians, and mechanics seniors, which focused on the development of knowledge workers (direct workers). The result of SWOT Analysis showed that unit business Aircraft Services should make an arranging program development for aircraft maintenance knowledge workers, namely: a training program for acquiring an Aircraft Maintenance Engineer License (AMEL), human resources procure system, career path, reward & compensation, and performance system. The finding was the lack of unit business Aircraft Services within preparing a business development plan program for aircraft maintenance wide-body because of corporate's response in supporting aircraft maintenance and technician/mechanics education center facilities were very slow. The conclusion was that unit business Aircraft Services, will have a competitive advantage for Aircraft maintenance narrow-body (Airbus & Boeing) if the result of strategy formulation has thoughtfully been implemented.